Presensi Online Menggunakan RFID pada Kartu Mahasiswa - Salhazan Nasution (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Information technology is no longer a complement, but a necessity in the academic world especially University. The presence of students in lectures is one important component in the learning process. The more students attend the class, the more students understand the lesson. In addition, the number of student attendance can also be a consideration for the lecturer in evaluating and taking action against the student. The current student attendance record is mostly still done manually by signing on a paper. The increasing number of students from year to year in University requires a system that can manage a large number of students’ data and the speed in obtaining access to information requires the university to build a system that can assist in the administration process in University. Online Presence System is a solution to overcome this, with this system then the recording of student presences can be done by scanning the RFID contained in the student card, no longer done manually using paper (paperless). This will assist lecturers and administrative staff in managing the recapitulation of student attendance and can be a consideration for lecturers in evaluating and taking action against the students concerned. In addition, this system will become a computerized data warehouse that stores the archives of student data in large numbers. Keyword : Online Presence System, RFID, Presentation, Attendance, Lecture